Can constraint targets facilitate industrial green production performance in China? Energy-saving target vs emission-reduction target. (1st February 2019) - Yao, Yue; Jiao, Jianling; Han, Xiaofei; Wang, Cuicui
Abstract: The roles played by constraint energy-saving and emission-reduction targets in the coordinated development of energy conservation, emission reduction, and economic growth are of great significance for China's sustainable progress. Applying a non-radial and non-oriented data envelopment analysis model incorporating innovation output and multiple undesirable outputs, this paper measures the green production performance (GPP) of China's industrial sectors from 2002 to 2015. Then, the effects of implementing an energy-saving target and an emission-reduction target on GPP are investigated through a Quasi-difference-in-differences method. The study shows that China's industrial GPP rose during 2002–2004 and then declined with fluctuations. GPP varies among industrial sectors, and the growth of desirable outputs dominates GPP. The energy-saving target positively affects industrial GPP in general, yet further dynamic analysis reveals that this positive effect is unstable and finally manifests a reverse impact in each five-year-plan period. The emission-reduction target adversely affects industrial GPP in general, while further dynamic analysis demonstrates that such a negative impact gradually expands over time. Therefore, the Chinese government should properly introduce market mechanisms, formulate comprehensive policy mix strategies, and increase the stability of industrial enterprises' green development to balance sustainable improvement of the industrial economy and the ecological environment. Highlights: GPP is measured by a DEA model comprising innovation and multiple undesirable outputs. Effects of an energy-saving target and an emission-reduction target on GPP are compared. The energy-saving target advances industrial GPP and yet undermines it gradually. The emission-reduction target tends to depress industrial GPP over time.